An effective method of verifying poles polarities in switched reluctance motors. Issue 2 (16th May 2019) - Han, Shouyi; Liu, Chuang; Sun, Xiaodong; Diao, Kaikai
Abstract : Purpose: This paper aims to propose an effective method to verify poles polarities of switched reluctance motors (SRMs). Different from the ways of detection poles polarities by permanent magnet in SRMs, the difference of self-inductance between different winding connections is used to verify the pole polarity. Design/methodology/approach: First, the winding connections with the forward and reverse series are proposed. The magnetic circuit models are established to analyze the flux linkage of different winding connections. Then, according to the difference of inductance characteristics, including the self-inductance and the mutual inductance affected by the adjacent poles, it is theoretically feasible to verify the polarity of each pole. Finally, the proposed method is verified by the simulation and experiment on a six-phase SRM. Findings: First, compared to the reverse series, the forward series can produce larger self-inductance when one phase is excited at the same current excitation, which can be used to verify the poles polarities of one phase with different winding connection. Second, the mutual inductance can be used to distinguish the winding connections. Third, the difference of the maximum self-inductance of the winding, which is composed of two adjacent windings, can be used to verify the polarities of the adjacent poles. Originality/value: This paper proposes an effective method to verify poles polarities of SRMs.